Effects of polyphenols in oil palm (Elaeis guineensis Jacq.) leaflet on in vitro rumen fermentation, biohydrogenation and microbial population in goats - Zakaria, Alif Aiman (2016)
The oil palm (Elaeis guineensis Jacq.) fronds (OPF) which are made up of petioles and leaves can be used as forage or feed supplement for small ruminants. Their effects on rumen fermentation, biohydrogenation and microbial populations have not been fully investigated. A methanolic extract of the leaves of the OPF was prepared and its polyphenol content and constituents were determined. The polyphenols in the OPLE were mainly tannins with lesser amounts of flavonoids and saponins. The effects of the methanol extract on in vitro rumen fermentation, biohydrogenation and microbial populations were assessed using rumen fluid obtained from goats. Two rumen fistulated (Bar-Diamond, Parma, ID, USA) Kacang crossbred male goats weighing 30.39 ± 0.74 Kg that were fed a diet comprising 50% alfalfa and 50% concentrate (DM basis) twice daily at 08:00 and 17:00 h were used in this study. The animals were housed individually in metabolic cages. Water and mineral blocks were available ad libitum. Fresh oil palm leaves were obtained from MARDI and immediately a methanolic oil palm leaf extract (OPLE) was prepared. Four treatment groups were designed namely a control group (CON), without OPLE (0%), (T1; low OPLE) containing 2.5 % OPLE, (T2; medium OPLE) containing 5% OPLE and (T3; high OPLE) containing 10% OPLE. A total of 0.25 g dried treatment feed material was placed in a 100 ml calibrated glass syringe and 30 ml of rumen fluid (from the rumen fistulated goats) were added into each syringe. All the syringes were incubated at 39 ˚C in a water bath incubator for 24 h. The volume of gas produced was measured at 0, 2, 4, 8, 10, 12 and 24 h post-incubation and the pH was recorded at 24 h post-incubation. The in vitro gas production of the OPLE methanolic extract after 24 h and the rate of in vitro gas production were significantly (P<0.05) higher in the CON compared with the treatment groups. In addition, there was a significant (P<0.05) decrease in rumen methane gas production in the treatment groups. There was no significant difference in the rate of in vitro biohydrogenation between the CON and treatment groups (P>0.05) although there was a decreasing trend in the latter. A Real-time Polymerase Chain Reaction technique was performed using the Bio-Rad CFX96 Touch (Bio-Rad Laboratories, Hercules, CA, USA) using optical grade plates to determine microbial populations and species. There was no significant difference (P>0.05) in the total bacteria and total protozoa population between the CON and treatment groups. However, there was a significant decrease (P<0.05) in the Butyrivibrio genus population in the treatment groups compared to the CON group. Similarly, there was a significant decrease (P<0.05) in the total methanogenic bacteria population in the treatment groups compared to the CON group. Although the OPLE methanolic extract reduced rumen total gas production and methane production, it did not affect rumen fermentation as reflected by normal pH values and volatile fatty acid (VFA) production. The overall results suggest that the OPLE can be used as a feed supplement for small ruminants as it does not affect rumen fermentation parameters, namely rumen pH and VFA production. In fact, it decreased methane production which would help in reducing pollution and tended to reduce biohydrogenation which should lead to the production of healthier meat. Further in vivo investigations are required to confirm these findings.